Gender and leadership: factors influencing election into student representative council and implications for sustainable development - Gwirayi, Pesanayi (Journal of Social Development in Africa, 2021)
The underrepresentation of women in leadership positions is symptomatic of every known society, and this is a matter of concern, at least when considered in the context of the equal opportunities discourse. The present study investigated the influence of gender on access to leadership positions in the Student Representative Council (SRC) among final year student teachers at a college in the Harare province of Zimbabwe. The study established the criteria that student teachers used when electing a fellow student to take up a position of leadership in the SRC, and analysed the explanations the students gave for considering a position as being suitable for male or female students or both sexes. Ninety students (50 male and 40 female) participated in the survey. An open-ended questionnaire was used to gather both quantitative and qualitative data. The results suggest that students have gendered perceptions towards particular SRC positions. Thus, a male student was more likely to be elected to the positions of SRC president or secretary general, while a female student was more likely to be elected to the positions of catering officer or treasurer. This appeared to confirm the prevailing view that males tended to control dominant and influential positions in the structures. The study however, concludes that, gender deconstruction is not only desirable, but feasible. The paper makes recommendations aimed essentially at further promoting the discourse on equal opportunities.